The Lived Experiences of Malaysian Young Adults Engaging in Nonsuicidal Self-Injury - Janet Ann, Fernandez; Rafidah Aga, Mohd Jaladin; Lau, Poh Li (Taylor & Francis Group, 2025)
Nonsuicidal self-injury is a perilous practice that is becoming more prevalent among young people worldwide. There might be cultural variations in some aspects of self-injury in terms of the underlying factors, triggers, and functions. This calls for an exploration of the development and maintenance of self-injury in the Malaysian context. The purpose of this research was to explore and describe the subjective experiences of Malaysian young adults engaging in self-injury. An interpretative phenomenological analysis was used as part of a qualitative phenomenological study design to give a comprehensive analysis of individuals’ lived experiences with self-injury. Purposive sampling was used to recruit 12 Malaysian young adults between the ages of 21 and 29 who engage in self-injury and are receiving psychotherapy or psychiatric treatment. There were two primary data collection methods: semi-structured interviews and document examination (participants’ drawings and participants’ diaries). Five superordinate themes emerged from the findings: (a) emotion dysregulation; (b) stressful life events; (c) intrapersonal function; (d) difficulty dealing with conflicts; and (e) suicidality. The lived experiences of young adults uncovered in this research have implications across the education, training, and practice of mental health.